Between Anthropogenic Influence and Resource Management: Impacts of Risks and Preservation Strategies in the Ikopa Watershed, Madagascar - Fidelio Arnold Ulrich; Razanamparany Bruno; Rejo Robert; Ratiarimananjatovo Narindra; Andrianjary Myriam; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2024)
The impacts of anthropogenic risks on water resource management underscore the necessity for a careful and adaptable approach to ensure long-term sustainability. In the Ikopa Watershed in Madagascar, numerous human activities present significant challenges. Water quality is impacted by pollution resulting from agricultural practices. Uncontrolled deforestation intensifies watershed degradation, jeopardizing the availability of water resources. Rapid urbanization and escalating human activities further contribute to the deterioration of water quality. The hypothesis posits that responsible exploitation of natural resources contributes to the preservation and sustainability of water resources in the Ikopa Watershed. This study concentrates on investigating potential anthropogenic risks that influence resource degradation and the perception of mitigation measures. The main objective of this section is to assess the anthropogenic risk factors contributing to water resource degradation in the watershed. The study employs change detection studies through remote sensing and GIS approaches, complemented by social analysis. This methodology aims to identify potential anthropogenic risks affecting responsible water resource management, along with an exploration of local mitigation strategies. The results underscored potential risks faced by the local population in the watershed, including challenges associated with agriculture, urbanization, inadequate drainage network management, and high population density. Binary logistic regression analysis reveals significant connections between anthropogenic risks and the mitigation strategies adopted by local communities in the Ikopa Watershed. The findings indicate that specific characteristics of degradation or local interventions can either positively or negatively influence the adoption of these strategies.